2010
DOI: 10.1111/j.1440-1630.2009.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the upper limb in acute stroke: The validity of hierarchal scoring for the Motor Assessment Scale

Abstract: Background/aim:  Stroke is the greatest contributor to disability in Australian adults and much of this disability results from a stroke‐affected upper limb. This study aimed to determine the validity of hierarchal scoring for the upper limb subscale of the Motor Assessment Scale (UL‐MAS) in acute stroke using Rasch analysis. Method:  This study applied Rasch analysis to 40 UL‐MAS assessment results across 25 subjects to determine the validity of the hierarchy of the three upper limb subsets: upper arm functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…For younger and older stroke survivors, the lines and dots tasks are more difficult to complete than other UL-MAS advanced hand activities. [9,10] Our study is the first to investigate the performance of healthy adults on these tasks. The lines task in particular was too difficult for many individuals in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For younger and older stroke survivors, the lines and dots tasks are more difficult to complete than other UL-MAS advanced hand activities. [9,10] Our study is the first to investigate the performance of healthy adults on these tasks. The lines task in particular was too difficult for many individuals in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[13,15] Subsequent Rasch analysis confirmed that for item eight, the motor behaviours are not ordered hierarchically. [9][10][11]16] Consistently, the two most difficult behaviours for stroke survivors to achieve on the advanced hand activities item are motor behaviours three and four. These two motor behaviours involve drawing 10 horizontal lines and making 10 dots in a set timeframe respectively and will hereafter be referred to as the 'lines task' and 'dots task'.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Недостатком шкалы FMA-UE является эффект «пола и потолка» (относится к ситуации, когда у больного име-ется незначительная степень двигательного функциони-рования, которую не выявляет шкала, или, наоборот, он получает максимальную оценку, но все же испытывает некоторые трудности при выполнении комплексных дви-жений) [14,18]. Положительными моментами являются отсутствие необходимости специального обучения, доста-точные простота и мобильность, эталонность данного те-ста.…”
Section: Fma-ueunclassified
“…Similarly, the hierarchical score for balanced sitting is based on graded increments of displacements of the person's center of mass. Since the hierarchical criteria for scoring the upper limb items are less obvious, several researchers have questioned [3, 5, 3033] the behavioral hierarchies for items 6 (upper limb), 7 (hand movements), and 8 (advanced aand activities).…”
Section: Introductionmentioning
confidence: 99%